2016
DOI: 10.1136/bmj.i2351
|View full text |Cite
|
Sign up to set email alerts
|

Potato intake and incidence of hypertension: results from three prospective US cohort studies

Abstract: Objective To determine whether higher intake of baked or boiled potatoes, French fries, or potato chips is associated with incidence of hypertension.Design Prospective longitudinal cohort studies.Setting Healthcare providers in the United States.Participants 62 175 women in Nurses’ Health Study, 88 475 women in Nurses’ Health Study II, and 36 803 men in Health Professionals Follow-up Study who were non-hypertensive at baseline.Main outcome measure Incident cases of hypertension (self reported diagnosis by heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 29 publications
1
81
1
3
Order By: Relevance
“…By applying substitution models it was shown that substituting one serving a day of baked/boiled/mashed potato for non-starchy vegetables was associated with a 7% reduced risk of hypertension in three US studies [10]. Moreover, substituting three servings weekly of baked/boiled/mashed potato, or French fries for whole grains was associated with a 5 or 17% reduced risk of T2D [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By applying substitution models it was shown that substituting one serving a day of baked/boiled/mashed potato for non-starchy vegetables was associated with a 7% reduced risk of hypertension in three US studies [10]. Moreover, substituting three servings weekly of baked/boiled/mashed potato, or French fries for whole grains was associated with a 5 or 17% reduced risk of T2D [51].…”
Section: Discussionmentioning
confidence: 99%
“…Six prospective cohort studies were included for all-cause mortality [29][30][31][32][33][34], seven prospective cohort studies (five reports) for CHD [14,[35][36][37][38], six prospective cohort studies (four reports) for stroke [14,37,39,40], two prospective cohort studies (one report) for heart failure [14], eight prospective cohort studies (seven reports) for CRC [41][42][43][44][45][46][47], eight prospective studies (seven prospective cohort studies, one RCT analysed as prospective cohort study) (six reports) for T2D [48][49][50][51][52][53], and four studies (two reports) for hypertension [10,54] (ESM Table 1). …”
Section: Esm Materials 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…White potatoes have been a staple food among many traditional diets of the Western world 24 (1). In recent years, the overall consumption of potatoes has declined in the USA, but 25 processed potato intake (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, consuming fried 186 potatoes more than twice a week was consistently associated with an increased mortality risk 187 in this population of older adults. chronic diseases, such as obesity (22,23), hypertension (24) and diabetes (6), which are also 218 powerful risk factors for CVD. One epidemiological study conducted in Sweden found no 219 association between fried potatoes intake and CVD mortality (8).…”
mentioning
confidence: 99%